2014
DOI: 10.12954/pi.14041
|View full text |Cite
|
Sign up to set email alerts
|

Role of cyclin D1 immunoreactivity and AgNOR staining in the evaluation of benign and malignant lesions of the prostate

Abstract: Purpose:Prostatic carcinoma is a common and growing public health problem. Histological evaluation is fairly adequate for assessing tumor differentiation, but tumor proliferative activity is difficult to measure. Increasing evidence suggests that the factors controlling cell cycle progression also modulate the rate of ribosome biogenesis. Despite the influence of cyclin D1 and argyrophilic nuclear organizer region (AgNOR) on prostate cancer proliferation, few studies have evaluated the diagnostic importance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
3
10
0
2
Order By: Relevance
“…Regarding PIN, eight cases (80%) showed positive Cyclin D1 expression. These results were close to previous studies by Gupta et al (2014) (1) and Anis et al (2013) (15) which reported positive nuclear Cyclin D1 expression in all studied PIN cases (100%).…”
Section: Discussion:-supporting
confidence: 92%
See 3 more Smart Citations
“…Regarding PIN, eight cases (80%) showed positive Cyclin D1 expression. These results were close to previous studies by Gupta et al (2014) (1) and Anis et al (2013) (15) which reported positive nuclear Cyclin D1 expression in all studied PIN cases (100%).…”
Section: Discussion:-supporting
confidence: 92%
“…In the present study, twenty three of the prostate cancer cases (92%) revealed positive nuclear staining for Cyclin D1. Nearly similar results were given by previous studies performed by Gupta et al (2014) (1) , Ozbek et al (2000) (10) , Ueda et al(2001) (13) and Anis et al (2013) (15) which reported positive nuclear Cyclin D1 expression ranging between 84.6% and 100%, but the results were in contrast with Kallakury et al(1997) (16) Shiraishi et al (1998) (17) and Drobnjak et al (2000) (18) which noticed positive nuclear Cyclin D1 expression in 22%, 30.3% and11% of their studied cases respectively. Different techniques and methods used for detection of Cyclin D1 in this study might explain the discrepancy in results.…”
Section: Discussion:-supporting
confidence: 92%
See 2 more Smart Citations
“…This silver staining allows a quantitative analysis of NORs, which are related to protein synthesis, being increased in number according to cell activity. This tool has been used to detect proliferation of neoplastic cells (Gupta et al., ); however, it has also been validated to assess the proliferative potential of granulosa cells of non‐neoplastic ovarian follicles (Silva et al., ).…”
Section: Introductionmentioning
confidence: 99%